Acute Myocardial Infarction Incidence, Mortality and Case Fatality in Santa Clara, Cuba, 2007–2008 - Alberto Morales (MEDICC Review, 2011)
INTRODUCTION Information on acute myocardial infarction inci- dence and mortality is essential for determining the ef cacy of the health system’s cardiovascular disease prevention activities; howev- er, in Cuba, suf cient data related to acute myocardial infarction are lacking, particularly at the local level. OBJECTIVE Describe acute myocardial infarction incidence, mortal- ity and case fatality rates from January 2007 through December 2008 in persons aged 45-74 in the municipality of Santa Clara, Villa Clara Province, Cuba. METHODS A retrospective descriptive study was conducted. The World Health Organization MONItorin g Trends and Determinants in CArdiovascular Disease Project (MONICA) methodology was used, but only in part, since out-of-hospital case fatalities were not investigated, resulting in insuf cient data for such cases. Cases of acute myocardial infarction covered under MONICA de nition 1 were included (non-fatal de nite, fatal de nite, fatal possible, and unclassi able deaths). Hospitalized patients were followed for 28 days. Incidence, mortality and case fatality rates in the population were calculated by age group (45–54, 55–64 and 65–74 years) and sex. Age-standardized incidence and mortality rates were calculated using the direct method, with the world population as a reference. RESULTS A total of 482 cases of acute myocardial infarction were registered. The percentage of cases of non-fatal de nite, fatal de nite, fatal possible and fatal with insuf cient data were 32%, 18.3%, 26.3% and 13.9% respectively. The cumulative age- standardized incidence per 100,000 population was 433 (95% CI 365–501) in men and 195 (95% CI 152–237) in women, while mor- tality per 100,000 population was 242 (95% CI 192–292) in men and 120 (95% CI 87–153) in women. Case fatality was 56.4% in men and 62.6% in women. Most fatal cases (65.6%) occurred out of hospital, a trend that was more marked in men (73.9%) than in women (51%). CONCLUSIONS Case fatality from acute myocardial infarction in Santa Clara residents was high, especially in women. Two thirds of fatalities occurred out of hospital, a higher proportion of these deaths in men. It is recommended that the AMI registry be com- pleted by investigating out-of-hospital case fatalities with insuf cient data; expanding it to include the 35-44 age group; and that the sup- ply of cardiac marker enzyme immunoassay test kits in Santa Clara be stabilized.